2011
DOI: 10.1159/000329443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Quality of Life of People with Dementia in Residential Care Facilities

Abstract: Aims: Our purpose was to compare recipient and caregiver perception of the quality of life (QoL) of people with dementia in residential care facilities and to identify the factors associated with their perception of QoL. Methods: Residents’ QoL was evaluated by both the patient and the caregiver, using the Quality of Life in Alzheimer’s Disease and several other indices. Results: The correlation between the self-rated QoL score and the staff-rated QoL score was low. Conclusions: The staff tended to underestima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 57 publications
1
42
1
Order By: Relevance
“…Even when sufficient communicative abilities were present, their severe cognitive impairments likely would have threatened the validity of self-reported results. Nonetheless, we should be aware that the QoL ratings could have been influenced by the professional caregivers' attitudes towards the resident and dementia [10,12,16] . Furthermore, we should be aware that correlations between the QUALIDEM subscales and NPI factors could have influenced the explained variance to some degree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when sufficient communicative abilities were present, their severe cognitive impairments likely would have threatened the validity of self-reported results. Nonetheless, we should be aware that the QoL ratings could have been influenced by the professional caregivers' attitudes towards the resident and dementia [10,12,16] . Furthermore, we should be aware that correlations between the QUALIDEM subscales and NPI factors could have influenced the explained variance to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased cognitive impairment and the presence of neuropsychiatric symptoms (NPS) were negatively associated with QoL in both community-dwelling people and nursing home residents with dementia [2,3,[5][6][7][8][9][10][11][12][13] . Of the NPS studied, especially depression was strongly associated with lower QoL scores [5,[7][8][9][10][11][14][15][16] . In addition, apathy, psychosis, and agitation are negatively associated with QoL [7,10,17] .…”
Section: Introductionmentioning
confidence: 95%
“…(AD) This research has shown that in patients higher depression scores, (2-4) the presence of behavioral disorders (5-7) and greater functional deficits (8,9) all have negative effects on QoLp. Among caregivers, poorer ratings of QoLp have been shown to be associated with functional deficits (10,11) and behavioral disorders (3,9) in the patient and with burden (3) and depression (12,13) in the caregiver.…”
mentioning
confidence: 99%
“…(AD) This research has shown that in patients higher depression scores, (2-4) the presence of behavioral disorders (5-7) and greater functional deficits (8,9) all have negative effects on QoLp. Among caregivers, poorer ratings of QoLp have been shown to be associated with functional deficits (10,11) and behavioral disorders (3,9) in the patient and with burden (3) and depression (12,13) in the caregiver. Some authors have also reported that perceptions of QoLp are affected by sociodemographic and contextual factors such as the caregiver's gender (14), his or her relationship to the patient, (15)(16)(17)) the patient's place of residence (2,3) or the environmental conditions.…”
mentioning
confidence: 99%
“…[53] It should be taken into account that the results of proxy measures, like in our study, can be lower and also may differ from the results of self-assessment. [42,54,55] …”
Section: Discussionmentioning
confidence: 99%